The Role of Policy Driven Incentives : A Cross-Country Analysis - Vagliasindi, Maria (World Bank, Washington, DC, 2012)
This paper presents new global evidence on the key determinants of public-private partnership investment in electricity generated by renewable energy based on a panel data analysis for 105 developing countries over a period of 16 years from 1993 to 2008. It aims to identify the key factors affecting the private investor's decision to enter renewable-based energy generation, through a probit analysis and the amount of investment sunk in this market segment, based on Heckman's sample selection analysis. One of the key results of the paper is that the market for renewable-based energy is strongly driven by supportive policies. Support policies serve not only to attract the entry of private investors, but also to determine the level of investment. In the latter case, its impact is less significant, suggesting the need over time to revisit the power of the incentive schemes, as well as the implied allocation of risks between the public and private sector to ensure that feed-in tariffs produce the desired amount of investment. In contrast, broader economy-wide governance factors, including control for corruption and degree of political competition, are considered by private investors mainly for taking the decision to enter into renewable-based generation. This reinforces the expectation that private investors seem to be adequately protected against their risks, so that once they have entered the market, they can accommodate the governance environment. Private investors in renewable-based energy also require technical and regulatory certainty about the availability of renewable-ready transmission resources, if they are to finance investments. Private investors entering the market look more at the size of the market rather than the income level, whereas when determining the level of investment they assess both the size and "affordability" level. This raises some concerns on the sustainability of support mechanisms and their financing, particularly when the incremental costs implied by renewable-based generation are passed through to consumers.